2024
DOI: 10.2147/cia.s453527
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anticoagulant Therapy and Frailty in the Elderly Patients with Atrial Fibrillation

Jiancao Ding,
Ying Sun,
Kan Zhang
et al.

Abstract: Objective This study explored whether anticoagulation is safe for frail and non-frail elderly patients who have nonvalvular atrial fibrillation (NVAF). Methods At hospital discharge, the anticoagulant regimen and frailty status were recorded for 361 elderly patients (aged ≥75 y) with NVAF. The patients were followed for 12 months. The endpoints included occurrence of thrombosis; bleeding; all-cause death; and cardiovascular events. Results At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Nevertheless, this study also has some limitations and several areas that need to be improved in the future, namely: (1) The readmission rate is also an important endpoint indicator, and we suggest that the authors incorporate this indicator into the research design in future studies; (2) Frailty is a dynamically changing symptom, and it is recommended that the authors need to measure this symptom repeatedly during the patients’ follow-up; (3) There are several areas in the text that need to be corrected: (a) Page 250, regarding the description of “The Cox regression analysis (which was adjusted for age, sex, daily activity, fall risk, cognition, nutrition, comorbidities, stroke, and bleeding risk) showed that anticoagulation tended to increase the bleeding risk (HR 0.584, 95% CI 0.337–1.013, P=0.056). Anticoagulation was not associated with thromboembolic events (HR 1.618, 95% CI 0.752–3.479, P=0.218), or all-cause death (HR 1.091, 95% CI 0.639–1.863, P=0.750; Table 4).” 1 , the values for HR, 95% CI or P are inconsistent with the results in Table 4 of page 251. The data in the text is incorrect.…”
Section: Dear Editorcontrasting
confidence: 57%
See 4 more Smart Citations
“…Nevertheless, this study also has some limitations and several areas that need to be improved in the future, namely: (1) The readmission rate is also an important endpoint indicator, and we suggest that the authors incorporate this indicator into the research design in future studies; (2) Frailty is a dynamically changing symptom, and it is recommended that the authors need to measure this symptom repeatedly during the patients’ follow-up; (3) There are several areas in the text that need to be corrected: (a) Page 250, regarding the description of “The Cox regression analysis (which was adjusted for age, sex, daily activity, fall risk, cognition, nutrition, comorbidities, stroke, and bleeding risk) showed that anticoagulation tended to increase the bleeding risk (HR 0.584, 95% CI 0.337–1.013, P=0.056). Anticoagulation was not associated with thromboembolic events (HR 1.618, 95% CI 0.752–3.479, P=0.218), or all-cause death (HR 1.091, 95% CI 0.639–1.863, P=0.750; Table 4).” 1 , the values for HR, 95% CI or P are inconsistent with the results in Table 4 of page 251. The data in the text is incorrect.…”
Section: Dear Editorcontrasting
confidence: 57%
“…1.10)." 1 the value for 95% CI of cardiovascular death is wrong. It should be "95% CI 0.49-0.55"; 2 (4) This study was only conducted in a single center with relatively small sample size, so the conclusion cannot represent the broader population.…”
Section: Disclosurementioning
confidence: 99%
See 3 more Smart Citations